Innovative Learning Strategies in Implementing The Independent Learning Curriculum - Sidharta Adyatma; Akhmad Munaya Rahman (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
The Independent Learning Curriculum is the main foundation in educational innovation in Indonesia, and challenges teachers to try to develop adaptive and responsive learning strategies to student needs, so to understand teachers' efforts to face these challenges, this study explores innovative learning strategies used by MGMP Geography teachers in Banjarmasin City in the context of the implementation of the Independent Learning Curriculum. The research employed a quantitative approach, involving structured interviews with 48 geography teachers who had implemented the Independent Learning Curriculum, as well as classroom observations and the analysis of learning documents. The analysis was carried out thematically to identify patterns of learning strategies that emerged. The results show that most geography teachers use a variety of innovative strategies, including the use of technology to support online and offline learning, the integration of field projects, and the implementation of problem-based learning. Adapting learning strategies to the needs of students and the challenges faced in implementing the Independent Learning Curriculum is crucial, as geography teachers play a vital role in leading learning transformation through a responsive and progressive approach. The results of the research are expected to provide valuable insights into effective learning practices within the new curriculum, and to lay a foundation for the development of more adaptive and relevant learning strategies.